2014
DOI: 10.1136/archdischild-2013-304747
|View full text |Cite
|
Sign up to set email alerts
|

Fresh frozen plasma use in the NICU: a prospective, observational, multicentred study

Abstract: FFP transfusion is a relatively frequent intervention in the NICU. In the present analysis, we found a remarkably high proportion of FFP transfusions given to non-bleeding neonates for indications not compliant with guideline recommendations. Platelet counts and coagulation studies were poor predictors of clinical bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 14 publications
3
45
2
2
Order By: Relevance
“…Previous studies report that up to 8% to 12% of neonates are transfused with FFP when all birthweights and gestational ages are included. At 15%, the higher use observed in our study likely reflects the inclusion of neonates born at less than 30 weeks' gestation only.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies report that up to 8% to 12% of neonates are transfused with FFP when all birthweights and gestational ages are included. At 15%, the higher use observed in our study likely reflects the inclusion of neonates born at less than 30 weeks' gestation only.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that 34% of the time, FP was administered prophylactically to correct an abnormal coagulation result for children who were not bleeding or due for an upcoming procedure . Prospective audits performed in the UK and Italy report that high proportions of FP transfusions are given for nonbleeding prophylactic indications. A systematic review assessing the role of plasma as a volume expander in the NICU found no evidence for its routine use in infants <32 weeks without cardiac compromise and insufficient evidence for preterm neonates with signs of cardiovascular compromise.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable uncertainty about appropriate use of FFP in neonates, which reflects the lack of evidence in this area. National audits have shown high proportions of FFP transfusions are given for prophylaxis: 42% of infant FFP transfusions in a UK audit (Stanworth et al , ) and 63% in a similar Italian audit (Motta et al , ). Prophylactic use of FFP, including prior to surgery, is of unproven benefit and uncertainty is compounded by the difficulty in defining a significant coagulopathy in this age group.…”
Section: Transfusions To Neonatesmentioning
confidence: 99%